2289. Accuracy of a Rapid Multiplex PCR Plus a Chromogenic Phenotypic Test Algorithm for the Detection of ESBL and Carbapenemase-Producing Gram Negatives Directly From Blood Cultures. (26th November 2018) - Vasoo, Shawn; Hon, Pei-Yun; Wee, Sharon S H; Chia, Jonathan W Z; Mendis, Shehara M; Izharrudin, Ezlyn; Lin, Ray J H; Chia, Po-Ying; Sim, Rees C S; Chen, Mark I C; Chow, Angela; Yoong, Joanne; et al.
Abstract: Background: We studied the multiplex PCR panel (BioFire Blood Culture ID panel, "BCID") with phenotypic testing using the Rosco Diagnostica Rapid ESBL Screen kit 98022 (RE) and the Neo-Rapid CARB kit 98024 (RC) for extended-spectrum β-lactamase (ESBL)/carbapenemase producing Gram negative bacilli (CPGNB) detection directly from blood culture bottles, in patients with Gram negative bacteremia. Methods: The RE and RC kits were evaluated in a verification phase with 98 blood cultures, comprising 43 spiked with GNB: 23 Escherichia coli, 9 Klebsiella pneumoniae, 7 Enterobacter cloacae, 2 Serratia marcescens, one Pseudomonas aeruginosa, one Acinetobacter baumanii complex with varying resistance genotypes (11 CTX-M-15, 5 CTX-M9, one SHV-18, one SHV-3, one TEM-10, 3 IMI, 4 IMP, 4 KPC, 2 NDM, one OXA-23+OXA-51-like, 3 OXA-232, one OXA-48, one SME-1, 2 VIM-1, 2 AmpC from reference and clinical isolate banks, and ATCC 25922), and 54 clinical blood cultures with GNB (5 phenotypic ESBL-positive, one KPC, 48 no known β-lactamase). In a prospective phase, a further 123 clinical blood cultures positive for GNB were tested simultaneously with the BCID, RE and RC kits. Results: In the verification phase, the RE kit detected 24/25 of ESBL-positive samples (sensitivity 96%, specificity 99%). The RE kit did not detect the 2 AmpC-producers, and was positive for a K. oxytoca isolate, which are known to produce chromosomally encoded β-lactamases. The RC kit detected 11/22 of CPGNB (sensitivity 50%, specificity 100%). It missed IMI, OXA-23+OXA-51-like, OXA-232, OXA-48, SME-1 and VIM CPGNB (weak carbapenemases), but detected NDM, KPC, IMP. In the prospective phase, the RE kit detected 20/20 ESBL-positive blood culture samples (sensitivity 100%). The single OXA-48 positive sample was detected by both the RE and RC kits. The 123 blood cultures had a total of 125 panel-represented targets detectable by BCID. The BCID detected 124 /125 (missed one K. pneumoniae in a polymicrobial bacteremia), and there were 2 Proteus false-positives (sensitivity 99%, specificity 98%). No KPC-positive samples were detected by BCID. Conclusion: An algorithm comprising the BCID and the RE/RC kits applied to positive blood cultures allows both rapid and accurate pathogen identification and detection of ESBLs and some carbapenemases (e.g., KPC, NDM, IMP). This may allow the institution of timelier, directed therapy. Disclosures: S. Vasoo, bioMerieux: Grant Investigator, Research support. Rosco Diagnostica: In-kind support, Research support. R. Banerjee, Accelerate Diagnostics, Biomerieux, BioFire: Grant Investigator, Research grant and Research support. R. Patel, CD Diagnostics, BioFire, Curetis, Merck, Hutchison Biofilm Medical Solutions, Accelerate Diagnostics, Allergan, and The Medicines Company: Grant Investigator, Research grant - monies paid to Mayo Clinic. Curetis, Specific Technologies, Selux Dx, GenMark Diagnostics, PathoQuest and Genentech: Consultant and Scientific Advisor, Consulting fee - monies paid to Mayo Clinic. ASM and IDSA: Travel reimbursement and editor's stipends, Travel reimbursement and editor's stipends. NBME, Up-to-Date and the Infectious Diseases Board Review Course: Varies, Honoraria. Mayo Clinic: Employee, Salary.